The Role of Monocytes and Macrophages in Autoimmune Diseases: A Comprehensive Review - Ma, Wen-Tao; Gao, Fei; Gu, Kui; Chen, De-Kun (Frontiers in Immunology, 2019)
Monocytes (Mo) and macrophages (Mφ) are key components of the innate immune system and are involved in regulation of the initiation, development and resolution of many inflammatory disorders. In addition, these cells also play important immunoregulatory and tissue-repairing roles to decrease immune reactions and promote tissue regeneration. Several lines of evidence have suggested a causal link between the presence or activation of these cells and the development of autoimmune diseases. In addition, Mo or Mφ infiltration in diseased tissues is a hallmark of several autoimmune diseases. However, the detailed contributions of these cells, whether they actually initiate disease or perpetuate disease progression, and whether their phenotype and functional alteration are merely epiphenomena are still unclear in many autoimmune diseases. Additionally, little is known about their heterogeneous populations in different autoimmune diseases. Elucidating the relevance of Mo and Mφ in autoimmune diseases and the associated mechanisms could lead to the identification of more effective therapeutic strategies in the future.